Nutritional risk at hospital admission is associated with prolonged length of hospital stay in old patients with COVID-19. Issue 12 (December 2022) - Mendes, Aline; Serratrice, Christine; Herrmann, François R.; Gold, Gabriel; Graf, Christophe E.; Zekry, Dina; Genton, Laurence
Summary: Background & aims: To investigate the association of nutritional risk at admission with the length of hospital stay (LOS) and mortality in older patients with COVID-19. Methods: Retrospective monocentric study in an acute geriatric hospital. Data were collected after an extensive review of medical records and the nutritional risk was assessed according to the Nutritional Risk Screening (NRS). Univariate and multivariate (adjusted for age, sex and comorbidity burden) Cox proportional-hazard and linear regression models were used to investigate the association with the above-mentioned outcomes. Results: Of a total of 245 patients (86.1 ± 6.4 yrs), 50.6% had a severe nutritional risk with an NRS≥5/7 at admission. Lower BMI, cognitive impairment and swallowing disorders were more prevalent in the patients with a higher NRS. A NRS≥5 was not associated with mortality but prolonged by more than 3 days the LOS among the 173 survivors (β 3.69; 0.71–6.67 95% CI; p = 0.016), with a discharge rate delayed by 1.8 times (HR 0.55; 0.37–0.83 95% CI; p = 0.101). Conclusion: Among the survivors of COVID-19 in an acute geriatric hospital, a NRS ≥5 at admission was associated with a longer LOS, but not with mortality.